2011
DOI: 10.1111/j.1440-1797.2011.01498.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient hypoxia‐inducible factor activation in rat renal ablation and reduced fibrosis with L‐mimosine

Abstract: There was a transient HIF-α activation in the remnant kidney of rats at the early stage following subtotal nephrectomy. L-mimosine administered in later stages re-activated HIF-α and reduced tubulointerstitial fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 28 publications
(75 reference statements)
2
29
0
Order By: Relevance
“…Simultaneously, there was transient HIF-␣ activation in the remnant kidney of rats at the early stage following subtotal nephrectomy, which also peaked at weeks 4 and 6. L-Mim administered in later stages reactivated HIF-␣ and ameliorated the progression of CKD and renal interstitial fibrosis (56,57). In the present study, we found the abundance of a miRNA, miR-29c, which is known to suppress the expression of extracellular matrix genes (22), was decreased in the rat remnant kidney model as well as in human kidneys with TIF from IgA nephropathy patients.…”
supporting
confidence: 48%
See 3 more Smart Citations
“…Simultaneously, there was transient HIF-␣ activation in the remnant kidney of rats at the early stage following subtotal nephrectomy, which also peaked at weeks 4 and 6. L-Mim administered in later stages reactivated HIF-␣ and ameliorated the progression of CKD and renal interstitial fibrosis (56,57). In the present study, we found the abundance of a miRNA, miR-29c, which is known to suppress the expression of extracellular matrix genes (22), was decreased in the rat remnant kidney model as well as in human kidneys with TIF from IgA nephropathy patients.…”
supporting
confidence: 48%
“…The nuclear expression of HIF-␣ was upregulated in the early stage after 5 ⁄6 nephrectomy when renal function was stable and returned to the basal level later, accompanied by impaired renal function and interstitial fibrosis (56). During the same progression time course in the remnant kidney model, abundance of miR-29c was decreased at week 2 and gradually restored from week 4 to week 6, coinciding with the peak of HIF-␣ upregulation.…”
Section: Mirna Profiles In the Renal Cortex Of 5 ⁄6 Nephrectomized Ramentioning
confidence: 70%
See 2 more Smart Citations
“…It was reported that HIF-α activation in CKD rats presents dynamic changes, as it is activated in early CKD stages and suppressed in the moderate and end-stage of CKD [95]. Thus, the administration of PHD inhibitors may improve renal function in more advanced stages of CKD, while in earlier stages, the PHD inhibitors may increase renal fibrosis due to upregulation of the HIF-1α subunit [22].…”
Section: Hif System In the Hyporesponsiveness To Erythropoiesis-stimumentioning
confidence: 99%